The nucleotide sequence of tobacco rattle virus RNA-2 (CAM strain). - Bergh, S T (1985)
The nucleotide sequence of the smaller genomic strand (RNA-2) of the bipartite tobacco rattle virus (CAM strain) has been determined. RNA-2 is capped at the 5' terminus and contains 1799 nucleotide residues. There is a single 223 codon long open reading frame extending from nucleotide 574 to 1242 which designates a protein of Mr 23,654. The derived amino acid composition, in percent, matches that previously determined for the virus capsid protein. The long open reading frame is flanked by 5' and 3' untranslated regions of 573 and 554 nucleotides, respectively. The 5' leader sequence contains two different sets of direct repeats, one of 119 nucleotides and the other of 76. It also contains 13 apparently unused AUG codons, four of which lie in the same frame as the capsid protein cistron. The 3' terminal sequence of RNA-2 is identical to that of the larger genomic strand (RNA-1) for 459 nucleotides.